A new genus and species of Plumariidae (Hymenoptera, Chrysidoidea) from western xeric Argentina - Diez, Patricia Alejandra (2007)
Mapluroides ogloblini, a new genus and species from the provinces of San Juan and La Rioja in western Argentina, are described. Descriptions, drawings and a discussion of its relationships to other plumariids are provided. The new taxon is closely related to Plumaroides Brothers and Maplurius Roig-Alsina.